A management plan for the sport fishery of Parachromis dovii (Pisces: Cichlidae) in Hule lake, Costa Rica - Tabash B., Farid A (2000)
A first attempt to regulate tbe fishing activity while preserving the species and its habitats is presented for Hule lake. We intensively sampled the "gu¡¡pote" between March 1996 and April 1997 using monofilament gill nets and a floating line, collecting 421 individuals. P. dovii biomass was relatively low; this species had a long life cycle (8-10 years) and tbe growth oscillation was low (C=O.3). Maximum life expectation was estimated at 12 years and the point of mínimum growtb coincided with the spawning that takes place between November and December. After sp¡¡wning, P. dovií take around seven montbs to reach recruitment size (54.6 mm). The length for sexual rnaturity was 134 mm Lt, whichjndicates that this s¡iecies is viable for reproduction soon after leaving the protection zones around the lagoon. "Guapote" sport fishing in the Hule lake is in equilibrium, the renewal rate is 80%. An increment in the actual fishery effort is not recommended, siilce it could seriously affect tbe natural renewal capacity of the stock.